Biomaterials in Costa Rica - Pérez Saborío, Edgar Eduardo (2025)
This research problematizes the field of biomaterials, examining their production rationale in the context of climate and ecological crises. The initial section outlines eleven fundamental categories to understand the production and research of biomaterials in Costa Rica, juxtaposed with theoretical discussions of global scope about how these categories are understood and conceptualized. The second part proposes a conceptual framework that organizes these approaches and redefines four key concepts. The research takes an interdisciplinary approach, integrating methods and subjects from the biological sciences, materials engineering, design, and art, along with tools from the social sciences and philosophy. It is concluded that conceptual distinctions extend beyond the scientific realm; biomaterial productions also imply political, socio-environmental, and ecological dimensions that must be differentiated through new concepts. Likewise, it is argued that inter/transdisciplinary research and the application of new biomaterials must constantly explore the concepts they engage with and critically assess the inherent production logic and its impact on the global environmental crisis and local ecosystems.